2021
DOI: 10.2147/ijgm.s312640
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Malpractice Litigation and Legislation Reform in Taiwan Over a 30-Year Period

Abstract: Background:The annual medical litigation rate has increased yearly since 1987 in Taiwan. Policy makers keep going medical legislation reforms. The effectiveness of legislation reforms to reduce malpractice litigation risk is uncertain. Objective: To determine whether medical legislation reform helps reduce the risk of medical litigation. Design, Setting, and Participants: This retrospective study used national data obtained from Ministry of Health and Welfare in Taiwan. The period analyzed was from 1987 to 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…25 Meanwhile, a more powerful and effective medical liability system is needed to reduce MD. 1,[26][27][28][29] This study showed that males, longer working hours/ week, and lower job satisfaction were associated with MD, which was in line with other studies and empirical evidence. Female physicians usually have more patience and better communication skills than their male counterparts.…”
Section: Discussionsupporting
confidence: 91%
“…25 Meanwhile, a more powerful and effective medical liability system is needed to reduce MD. 1,[26][27][28][29] This study showed that males, longer working hours/ week, and lower job satisfaction were associated with MD, which was in line with other studies and empirical evidence. Female physicians usually have more patience and better communication skills than their male counterparts.…”
Section: Discussionsupporting
confidence: 91%
“…As a recent study revealed, the percentage of criminal cases was 4.7 times higher than that of civil cases in medical disputes litigation, however, the percentage of "no-fault" cases was 4.5 times higher than that of "negligence" and "possible negligence" cases. 25 To guide patients to use adequate channels for complaints and solve disputes, policymakers in Taiwan proposed the Medical Malpractice Resolution and Compensation Act as the alternative dispute resolution for medical malpractice litigations in 2012, and the annual medical litigation rate declined by 38% from 2012 to 2018. 25 However, when we conducted this study at the end of 2017, the fear of litigation and criminal procedures was still quite prevalent among our interviewees.…”
Section: Discussionmentioning
confidence: 99%
“…25 To guide patients to use adequate channels for complaints and solve disputes, policymakers in Taiwan proposed the Medical Malpractice Resolution and Compensation Act as the alternative dispute resolution for medical malpractice litigations in 2012, and the annual medical litigation rate declined by 38% from 2012 to 2018. 25 However, when we conducted this study at the end of 2017, the fear of litigation and criminal procedures was still quite prevalent among our interviewees. This is probably because frequent use of criminal law channels was considered as a hostile reaction of patients and intimidating to physicians.…”
Section: Discussionmentioning
confidence: 99%
“…However, research on medical dispute resolution methods has focused more on litigation [29][30][31][32][33][34][35]; some studies have emphasized the role of mediation, but research into the characteristics, e ciency, and in uencing factors of TPM in resolving medical disputes using a large number of detailed cases is lacking [19,27,29,36]. Therefore, we analyzed TPM practices using data from 5,948 cases in Chinese public hospitals from 2014 to 2019 in Gansu, a western province in China.…”
Section: Introductionmentioning
confidence: 99%